The Role of Customer Satisfaction As A Mediator: The Relationship Between Product Quality, Service Quality, And Information Quality Towards Loyalty - Dewi Wulan Noviasari; Syarif Hidayatullah; Ery Sulistyorini; Stella Alvianna; Ryan Gerry Patalo (Business Management Research, 2025)
The purpose of this study is to examine how product quality, service quality, and information quality affect customer loyalty, with customer satisfaction acting as an intermediary variable. This research specifically targets moisturizer products from “The Originote” through TikTok Shop. The study's population includes users of the TikTok app, though the exact number is not specified. A total of 125 respondents were sampled. A quantitative approach was employed, collecting data via surveys and interviews for primary data, alongside literature for secondary data. The analysis was conducted using multiple linear regression with two models. The findings reveal that both product quality and service quality positively and significantly influence customer satisfaction, while information quality does not have a notable effect. Additionally, product quality and customer satisfaction are shown to significantly enhance customer loyalty, whereas service quality and information quality do not. Customer satisfaction serves as a mediator that reinforces the impact of service quality and information on customer loyalty. These results underscore the significance of prioritizing product and service quality to foster customer loyalty. The implications of this research can help companies develop more effective marketing strategies, especially in utilizing the TikTok platform to boost customer satisfaction and loyalty.